2002
DOI: 10.1002/tal.189
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of shear‐lag effects in framed‐tube structures with internal tube(s)

Abstract: The shear-lag phenomenon is a critical consideration in high-rise building analysis and design. The shear-lag behaviour of framed-tube (including tube, tube-in-tube and tubes-in-tube constructions) is investigated for the behavioural characteristics of the structures and their performance in relation to the various structural parameters. The stiffness factor in terms of the axial stiffness of the columns and the bending stiffness of columns and beams is chosen as a main parameter to explain the shear-lag pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The effectiveness was demonstrated through a comparison with FE results for various tall and high‐rise buildings. Other authors (Lee et al ., ; Myoungsu et al ., ) have conducted parametric studies on the variation in the axial and bending stiffness properties of columns and beams, therein reporting that the axial stiffness of the columns is the most influential factor in the tube action as well as in the shear lag behavior, whereas the bending stiffness of the columns and beams had little impact, perhaps due to the tube‐to‐tube interaction. Other studies (Swaddiwudhipong et al ., ; ) have stressed that the effect of axial deformation in the frame within frame‐shear wall systems should also be considered for tall and/or slender buildings, and the effect of the axial force in the column should be included for arrangements that include a termination of core walls in the lower portion of the building.…”
Section: Introductionmentioning
confidence: 96%
“…The effectiveness was demonstrated through a comparison with FE results for various tall and high‐rise buildings. Other authors (Lee et al ., ; Myoungsu et al ., ) have conducted parametric studies on the variation in the axial and bending stiffness properties of columns and beams, therein reporting that the axial stiffness of the columns is the most influential factor in the tube action as well as in the shear lag behavior, whereas the bending stiffness of the columns and beams had little impact, perhaps due to the tube‐to‐tube interaction. Other studies (Swaddiwudhipong et al ., ; ) have stressed that the effect of axial deformation in the frame within frame‐shear wall systems should also be considered for tall and/or slender buildings, and the effect of the axial force in the column should be included for arrangements that include a termination of core walls in the lower portion of the building.…”
Section: Introductionmentioning
confidence: 96%
“…Hence, their columns are more evenly stressed than in the single tube structure and their contribution to the lateral stiffness is greater. Kristek and Bauer (1993), Singh and Nagpal (1995) and Lee et al (2002) extended the study to examine the shear lag behavior of framed-tube buildings. In a framed-tube system, columns play a role in making up discontinuous segments of the building tube section that are potentially available for the tube action, and the role of spandrel beams is to effectively engage the discontinuous section segments together, so that they can be fully utilized for the tube action.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2002) conducted a parametric study by changing the axial and bending stiffness properties of columns and beams, and reported that the axial stiffness of the columns was the most influential factor on the tube action as well as the shear lag behavior, while the bending stiffness of the columns and beams were of little impact perhaps due to the tube-totube interaction. However, the variables used in this parametric study appear to be unreasonable from a practical standpoint, because changing one stiffness property of a member typically accompanies changes in other stiffness properties of the member (and even other members in some cases) in real design, which was not taken into account in Lee et al (2002). For example, varying the column sectional dimension parallel to the frame direction affects not only the stiffness of the column, but also the stiffness of the beams framing into the column (by reducing the clear span length of the beams).…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple internal tubes reduces the effect of shear lag in the tubes, induces more effective participation of internal columns in resisting lateral forces and offers additional lateral stiffness to the structure. Kristek and Bauer [4], Singh and Nagpal [5] and Lee et al [6] extended the study to examine the shear lag behaviour of single and multiple framed-tube buildings. …”
Section: Introductionmentioning
confidence: 99%